Comparison of microRNAs in adipose and muscle tissue from seven indigenous Chinese breeds and Yorkshire pigs. (21st July 2019) - Liang, Y.; Wang, Y.; Ma, L.; Zhong, Z.; Yang, X.; Tao, X.; Chen, X.; He, Z.; Yang, Y.; Zeng, K.; Kang, R.; Gong, J.; et al.
Summary: Elucidation of the pig microRNAome is essential for interpreting functional elements of the genome and understanding the genetic architecture of complex traits. Here, we extracted small RNAs from skeletal muscle and adipose tissue, and we compared their expression levels between one Western breed (Yorkshire) and seven indigenous Chinese breeds. We detected the expression of 172 known porcine microRNAs (miRNAs) and 181 novel miRNAs. Differential expression analysis found 92 and 12 differentially expressed miRNAs in adipose and muscle tissue respectively. We found that different Chinese breeds shared common directional miRNA expression changes compared to Yorkshire pigs. Some miRNAs differentially expressed across multiple Chinese breeds, including ssc‐miR‐129‐5p, ssc‐miR‐30 and ssc‐miR‐150,  are involved in adipose tissue function. Functional enrichment analysis revealed that the target genes of the differentially expressed miRNAs are associated mainly with signaling pathways rather than metabolic and biosynthetic processes. The miRNA–target gene and miRNA–phenotypic traits networks identified many hub miRNAs that regulate a large number of target genes or phenotypic traits. Specifically, we found that intramuscular fat content is regulated by the greatest number of miRNAs in muscle tissue. This study provides valuable new candidate miRNAs that will aid in the improvement of meat quality and production.